AKTIVITAS l'ENGASUHAN SEBAGAIPREDIKTOR TINGKAHLAKU BERMASALAH - Rita Eka Izzaty (Jurnal Cakrawala Pendidikan, 2008)
Behavior problem is often observed among clilldren. Ecological Theory depictsinteraction of environmental factors which ihflllence children's development.Earenting practices is one of factors that has been identified as predictors of theprpblem.emotional and social support, monitoring, and discipline are centraldimensions ofparental practices that are linked with children's adjustment,development,and welbbeing. A meta -analysis of 51 studies examining therelationship betweenparenting practices and externalizing behavior problems,'inyolving 13 researchers and 49564 subjects, is reported. This analysis extendsprevious works in the sense that it integrates diverse findings by correcting errorsQf sampling and measurements. The results show that several dimensions inparenting practices, namely emosional and social support, monitoring, anddiscipline are significant predictQrs of externalizing behavior problems.